A Rare Case Report of Endovascular Therapy for Basilar Artery Occlusion in a Young Adult with Marfan Syndrome. (April 2022) - Zhu, FeiYan; Zhang, ZhenZhong; Lv, Chenling; Wang, BaiChen; Wei, Fuquan
Basilar artery occlusion (BAO) is one of the most devastating types of ischaemic stroke and is identified by using computed tomography (CT) angiography. Marfan syndrome is an autosomal dominant disorder involving multisystem connective tissue, and the neurological complications are relatively rare. In this article, we report a case of a young Marfan syndrome patient complicated with BAO ischaemic stroke. The patient was an 18-year-old man with right hemiparesis, aphasia and impaired consciousness. CT angiography of the brain showed an occlusion distal to the basilar artery. Endovascular therapy including intravenous thrombolysis and mechanical thrombectomy (MT) was administered to this patient inside the therapeutic window. The patient had a favourable clinical outcome after endovascular therapy. Marfan syndrome may be a rare cause of ischaemic stroke with BAO. In addition, our report provides some evidence that can be used as a reference when planning therapeutic strategies for BAO patients with Marfan syndrome.